2022
DOI: 10.1136/annrheumdis-2021-221795
|View full text |Cite
|
Sign up to set email alerts
|

2022 American College of Rheumatology/European Alliance of Associations for Rheumatology classification criteria for granulomatosis with polyangiitis

Abstract: ObjectiveTo develop and validate revised classification criteria for granulomatosis with polyangiitis (GPA).MethodsPatients with vasculitis or comparator diseases were recruited into an international cohort. The study proceeded in five phases: (1) identification of candidate criteria items using consensus methodology, (2) prospective collection of candidate items present at the time of diagnosis, (3) data-driven reduction of the number of candidate items, (4) expert panel review of cases to define the referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
162
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(174 citation statements)
references
References 17 publications
(24 reference statements)
1
162
0
11
Order By: Relevance
“…We read the comments by Pimentel-Quiroz et al with interest1 and agree it is important to test the performance characteristics of the 2022 ACR/EULAR Classification Criteria for the ANCA-associated vasculitides (AAV) in different populations around the world 2–4. These efforts are needed to understand whether regional differences in disease expression and clinical evaluation impact the utility of the new criteria in specific populations.…”
mentioning
confidence: 97%
“…We read the comments by Pimentel-Quiroz et al with interest1 and agree it is important to test the performance characteristics of the 2022 ACR/EULAR Classification Criteria for the ANCA-associated vasculitides (AAV) in different populations around the world 2–4. These efforts are needed to understand whether regional differences in disease expression and clinical evaluation impact the utility of the new criteria in specific populations.…”
mentioning
confidence: 97%
“…In this issue of Arthritis & Rheumatology , the 2022 American College of Rheumatology (ACR)/European Alliance of Associations for Rheumatology (EULAR) classification criteria for granulomatosis with polyangiitis (GPA) (4), microscopic polyangiitis (MPA) (5), and eosinophilic granulomatosis with polyangiitis (EGPA) (6) are presented. They are based on the analysis of the most ambitious prospective cohort study ever on vasculitis, the Diagnostic and Classification Criteria in Vasculitis (DCVAS) project, involving almost 7,000 patients from 136 sites worldwide.…”
mentioning
confidence: 99%
“…As a consequence, the criteria of ANCA detection and type outweighed the other (diagnostically relevant) typical characteristics of small‐vessel vasculitis, such as certain clinical manifestations (e.g., constitutional symptoms or skin lesions) or histologically confirmed pauci‐immune glomerulonephritis, which are either not included among the new classification criteria or were accorded relatively low weights. Patients with ANCA‐negative limited GPA, for example, would hardly fulfill the new classification criteria and therefore be missed if the criteria were (mis)used for diagnostic purposes (4).…”
mentioning
confidence: 99%
“…The new classification criteria for antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) have been eagerly anticipated since the publication of the provisional criteria in 20171 and thus they are quite welcomed 2 3. Limitations of the previous criteria used for these conditions include the low sensitivity of the 1990 American College of Rheumatology (ACR) classification criteria, the fact that the patient’s ANCA status had not been included, that there were no previous classification criteria for microscopic polyangiitis (MPA), and the fact that the number of criteria rather than a weighted criteria were used.…”
mentioning
confidence: 99%
“…Given these considerations, we read with great interest the articles on the new classification criteria for GPA and MPA by Robson et al and Suppiah et al , respectively,2 3 which have shown to have good sensitivity and specificity. These criteria have been validated by the Diagnostic and Classification Criteria in Vasculitis (DCVAS) project which recruited 6991 participants (among patients with AAV and comparator diseases) from 132 sites in 32 countries around the world.…”
mentioning
confidence: 99%